Positive psychology and its role within mental health nursing. (2nd May 2019) - Macfarlane, Jan
Abstract : This is the second article in a series of articles that explores the meaning of positive psychology and the importance of applying the latest research findings for the wellbeing of the mental health workforce. There will be an historical outline of positive psychology, showing it is not as 'new' as people may believe. The article sets the context and explains key terms through the underpinning theoretical work of Martin Seligman. This is followed by an explanation of how it is relevant to mental health nursing, five interventions mental health nurses can use to help encourage positive thinking, and a discussion on making new skills via neuroplasticity. The practical tasks provided in the boxes throughout the article will help the reader to understand what happiness means to an individual and how it can be developed with evidence-based, user-friendly effective exercises.